A genome‐wide association study of recipient genotype and medium‐term kidney allograft function. (21st February 2013) - O'Brien, Robert P.; Phelan, Paul J.; Conroy, Judith; O'Kelly, Patrick; Green, Andrew; Keogan, Mary; O'Neill, Derek; Jennings, Susan; Traynor, Carol; Casey, Jillian; McCormack, Mark; Conroy, Ronan; et al.
Abstract Background We examined, through genome‐wide association studies (GWAS), the correlation between recipient genetic variation and renal function at five yr. Methods Our cohort contained 326 Irish, first time, kidney‐only, deceased donor, transplant recipients on calcineurin inhibitors (263 had a functioning graft at five yr) between 1993 and 2002. Outcomes were creatinine at five yr and long‐term graft function. Results Two variants were identified showing borderline genome‐wide significance – one on chromosome 18 (p = 4.048e‐08, rs6565887) and another on chromosome 14 (p = 7.631e‐08, rs3811321). Individually, the two SNPs explained up to 8.8% and 11.29% of five‐yr creatinine variance, respectively, while together they explained up to 17.4% of trait variance. Both variants were predictors of long‐term allograft function (p = 0.004, 70% vs 30% survival at 10 yr). The chromosome 14 variant is located in the intergenic region of the T‐Cell Receptor Alpha locus. Conclusions Using a genome‐wide approach, we have identified two associations with five‐yr creatinine levels in renal transplant recipients treated with calcineurin inhibitors. Independent replication is now warranted to clarify the clinical significance of these results.